QoG EU Regional Data - Charron, Nicholas; Holmberg, Sören; Rothstein, Bo; Khomenko, Anna; Svensson, Richard; Dahlberg, Stefan (University of Gothenburg, 2013)
The QoG Institute is an independent research institute within the Department of Political Science at the University of Gothenburg. Overall 30 researchers conduct and promote research on the causes, consequences and nature of Good Governance and the Quality of Government - that is, trustworthy, reliable, impartial, uncorrupted and competent government institutions.

The main objective of our research is to address the theoretical and empirical problem of how political institutions of high quality can be created and maintained. A second objective is to study the effects of Quality of Government on a number of policy areas, such as health, the environment, social policy, and poverty.

The QoG EU Regional Data is a dataset consisting of approximately 450 variables covering three levels of European regions - Nomenclature of Territorial Units for Statistics (NUTS): NUTS 0 (country), NUTS 1 (major socio-economic regions) and NUTS 2 (basic regions for the application of regional policies). QoG Regional Data has been divided into three datasets and these are available in time-series version (from 1990 to 2015) and the unit of analysis is region-year (e.g. Stockholm-2013). The first combined dataset is referred to as "long" and the list of units for analysis contains regions at all levels of NUTS. The other two are referred to as "wide" and include NUTS 1, NUTS 2 respectively as analysis units and variables represent values for both the current level and the lower levels.

Purpose:

The primary aim of QoG is to conduct and promote research on corruption. One aim of the QoG Institute is to make publicly available cross-national comparative data on QoG and its correlates.

EU QoG Index (EQI) is a measure of corruption at a regional level in the EU. The index is based on 16 variables from the survey.

When using QoG Basic data, please cite as follows (don´t forget to also cite the original source):
Charron, Nicholas, Stefan Dahlberg, Sören Holmberg, Bo Rothstein, Anna Khomenko & Richard Svensson. 2016. The Quality of Government EU Regional Dataset, version Sep16. University of Gothenburg: The Quality of Government Institute, http://www.qog.pol.gu.se

QoG-institutet är ett oberoende forskningsinstitut som tillhör Statsvetenskapliga institutionen vid Göteborgs universitet. Sammanlagt är det ungefär 30 forskare som bedriver internationell forskning om orsaker till och konsekvenserna av korruption och samhällsstyrningens kvalitet.

Forskningen fokuserar på det teoretiska och empiriska problemet hur politiska institutioner av hög kvalitet kan skapas och upprätthållas, samt studerar effekterna av samhällsstyrningens kvalitet på ett antal olika politikområden, som exempelvis hälsa, miljö, socialpolitik och fattigdom.

QoG EU Regional Data är en datamängd som omfattar cirka 450 variabler för europeiska regioner på tre nivåer - Nomenklatur för statistiska territoriella enheter (NUTS): NUTS 0 (länder), NUTS 1 (större socioekonomiska områden) och NUTS 2 (grundläggande områden för tillämpning av regionalpolitik). QoG Regional Data har delats in i tre dataset och dessa finns tillgängliga som tidsserier (från år 1990 till och med 2015) och enheten för analys är region-år (t. ex. Stockholm-2013). Det första kombinerade datasetet benämns som "long" och behandlar samtliga NUTS-nivåer. De andra två benämns som "wide" och innefattar NUTS 1, respektive NUTS 2 som analysenhet och variabler representerar värden för både den aktuella nivån och de lägre nivåerna.

Syfte:

QoG:s huvudsakliga syfte är att bedriva och främja forskning om korruption. Ytterligare ett syfte med institutet är att offentliggöra nationellt gränsöverskridande och jämförbara data.

EU QoG Index (EQI) är ett mått för korruption på regional nivå i EU. Indexet bygger på 16 variabler ifrån undersökningen.

When using QoG Basic data, please cite as follows (don´t forget to also cite the original source):
Charron, Nicholas, Stefan Dahlberg, Sören Holmberg, Bo Rothstein, Anna Khomenko & Richard Svensson. 2016. The Quality of Government EU Regional Dataset, version Sep16. University of Gothenburg: The Quality of Government Institute, http://www.qog.pol.gu.se
QoG EU Regional Data
Keywords: EUROPEAN UNION; EUROPEISKA UNIONEN; STATE CONTROL; STATLIG STYRNING; CORRUPTION; KORRUPTION; DATA; DATA; BUREAUCRACY; BYRÅKRATI; PUBLIC ADMINISTRATION; OFFENTLIG FÖRVALTNING; GOVERNMENT ORGANIZATIONS; STATLIGA ORGANISATIONER; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap